The Use of Web-Based Blooket in Improving Students Mastery of English Vocabulary - Eva Yanti; Nuzulul Isna (Universitas Islam Negeri Palopo, 2025)
This study investigates the effectiveness of using Blooket, a web-based educational game, to improve English vocabulary mastery among fifth-grade students at SDN 6 Susoh, Southwest Aceh. Employing a pre-experimental one-group pretest-posttest design, the study involved 30 students who received four sessions of Blooket-based learning focused on family member vocabulary. Data were collected using a 20-item multiple-choice test administered before and after the intervention. Analysis through descriptive statistics and a paired sample t-test revealed a significant increase in students’ vocabulary scores from a mean of 37.53 on the pretest to 74.83 on the posttest, with a p-value of <0.001. These findings suggest that Blooket effectively enhances vocabulary mastery by increasing student engagement and reducing achievement gaps through interactive, gamified learning. Despite the study’s limitations—such as the absence of a control group and a small sample size—Blooket demonstrates promise as a practical and motivating tool for primary school vocabulary instruction, particularly in rural contexts where traditional methods may fall short.